Mechanical degradation of sugar palm crystalline nanocellulose reinforced thermoplastic sugar palm starch (TPS)/poly (lactic acid) (PLA) blend bionanocomposites in aqueous environments - Nazrin, Asmawi; Mohd Sapuan, Salit; Mohd Zuhri, Mohamed Yusoff; Mohamed Amin Tawakkal, Intan Syafinaz; Ilyas, Rushdan Ahmad (De Gruyter, 2023)
The concerning issue regarding petrochemical plastic wastes had prompted scientists and researchers to develop biodegradable plastic in effort to tackle environmental pollution. Alternative bioresources such as poly (lactic acid), sugar palm starch and nanocellulose fibre were utilized in producing cheap, biodegradable and sustainable plastic with satisfactory mechanical properties for food packaging application. In this study, sugar palm crystalline nanocellulose (SPCNC) was priorly dispersed in thermoplastic sugar palm starch (TPS) before melt blended with poly (lactic acid) (PLA) and later compress moulded into a sheet form. Initial biodegradation test of PLA100 and all PLA/TPS blends bionanocomposite samples indicated that PLA60TPS40 has the least variation in weight loss due to the good miscibility between TPS and PLA promoting the reinforcement of SPCNC. Greater weight losses in seawater (17.54%), river water (18.97%) and sewer water (22.27%) result in greater mechanical degradation as observed at the reduction of tensile strength from 12.11 MPa to 2.72 MPa in seawater, 1.48 MPa in river water and 0.40 MPa in sewer water. Similarly, higher weight losses in seawater (22.16%), river water (21.6%) and sewer water (23.09%) correlated with the reduction of flexural strength from 18.37 MPa to 3.5 MPa in seawater, 3.83 MPa in river water and 3.6 MPa in sewer water. The scanning electron microscope (SEM) images of tensile fracture morphology demonstrated clear porous structure due to the removal of starch particles by microbial activity. The homogenous structure of PLA60TPS40 had a steady and consistent degradation, which wholly diminished the interfacial adhesion that led to mechanical properties losses. The mechanical strength reduction clarified that the biodegradation rate within the media used might be able to resolve the excessive non-biodegradable plastic waste in open waters.